2016
DOI: 10.12973/eurasia.2017.00624a
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Using Augmented Reality Apps in Teaching the English Alphabet to Kindergarten Children: A Case Study in the State of Kuwait

Abstract: This experimental research study scrutinized the effectiveness of using augmented reality (AR) applications (apps) as a teaching and learning tool when instructing kindergarten children in the English alphabet in the State of Kuwait. The study compared two groups: (a) experimental, taught using AR apps, and (b) control, taught using traditional face-to-face methods. A total of 42 (i.e., 21 in the experimental group and 21 in the control group) preschoolers enrolled in the public educational system participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 14 publications
2
79
0
5
Order By: Relevance
“…Mobile Augmented Reality (MAR) based on Doswell et al (2006) is a term used when equipment through which we achieve AR is small in size and typically easy to carry a smartphone or a tablet. The result of those previous studies are also relevant with the studies conducted by Bedder (2012), Marc C et al (2016, Diegmann et al (2011), and Saffar et al (2016), in which the result of their study showed that AR was effective to improve students' vocabulary mastery.…”
Section: Discussionsupporting
confidence: 60%
“…Mobile Augmented Reality (MAR) based on Doswell et al (2006) is a term used when equipment through which we achieve AR is small in size and typically easy to carry a smartphone or a tablet. The result of those previous studies are also relevant with the studies conducted by Bedder (2012), Marc C et al (2016, Diegmann et al (2011), and Saffar et al (2016), in which the result of their study showed that AR was effective to improve students' vocabulary mastery.…”
Section: Discussionsupporting
confidence: 60%
“…Besides, AR picture books were attractive for children and they perceived them as magical and enjoyable. Secondly, Safar et al [42] investigated effectiveness of using AR for teaching English alphabet lesson with flash cards to kindergarten children. A mobile application was developed for using flash cards.…”
Section: Using Augmented Reality In Early Childhood Educationmentioning
confidence: 99%
“…A wide range of studies have been conducted on integrating AR into the learning of diverse curricular areas, such as science Kamarainen et al, 2013), language learning Moralishvili & Akaki, 2014;Solak & Cakir, 2015), architecture (Megahed, 2014), ICT (Sampaio & Almeida, 2016), chemistry (Prokopenko, 2017), mathematics and geometry (Bujak et al, 2013;Sommerauer & Müller, 2014), and geography (Chen & Wang, 2015;Hsiao et al, 2016). Various research studies have also been conducted at different educational levels: early childhood education (Cascales, Pérez-López, & Contero, 2013;Safar, 2017;Yilmaz, 2016), primary schools (Alkhattabi, 2017), secondary schools ( Bressler & Bodzin, 2013;, and university level and higher education (Rodríguez, 2013). This diverse literature reveals the recent increasing interest by various researchers to examine the effectiveness and potential affordances of AR in leveraging the teaching and learning quality in meaningful, successful educational contexts.…”
Section: Augmented Reality In Educationmentioning
confidence: 99%
“…This process of augmenting the learning context together with the collaborative, multi-user learning environment allows for vivid interactions and boosted communications among students. Using a combination of multimedia and animation elements appeal students' minds more than merely use of text and images in traditional study books (Diegmann, Schmidt-kraepelin, Eynden, & Basten, 2015;Safar, 2017;Shirazi & Behzadan, 2013). Since the biggest motive of teachers is to capture the attention of learners throughout the learning session in appealing and engaging context, students often describe their AR-based learning as highly interesting and interactive.…”
Section: Increased Attentionmentioning
confidence: 99%
See 1 more Smart Citation